Bauxite processing and employment : a case study. - Mc Coy, James P. (1990)
Estimates the effects of increased domestic processing of bauxite on sectoral and aggregate employment in Jamaica. Increased alumina refining only moderately increases aggregate employment while aluminium smelting could have a very large impact.